Developing English Speaking Materials for Islamic High School Students: Learning Needs and Practicality - Purwati, Diana; Yasin, Ilyas; Karmila; Arifudin (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The development of English speaking materials that meet with students’ learning specific needs of Islamic high school students is essential for enhancing their communicative competence while aligning with their cultural and educational contexts. Even though learning resources for speaking skill have been developed, the learning resource, textbook, that design for enhancing EFL students’ speaking skill and meet with their learning needs at Islamic Institution is still rare. This study aims to design, validate, and assess the practicality of English speaking materials that support the speaking skill of these learners. Using Research and Development study (R&D) consisting of four stages: define, design, develop, and dessiminate. Thirty students were involved in this study at one of Islamic Senior High Schools in West Nusa Tenggara Provinces, Indonesia. A comprehensive needs analysis was conducted through surveys and classroom observations to identify students’ linguistic requirements, preferences, and challenges. The findings showed that the majority of the students aim to master the speaking skill that incorporating Islamic themes and communicative activities as it meets with their context and culture. Expert evaluations confirmed the validity of the learning materials, highlighting their linguistic accuracy, relevance, and cultural appropriateness which clearly showed 93%, and 90% respectively. The study concludes that the development of learning resources that integrating Islamic values and communicative language teaching principles is fundamental for Islamic senior high school students to support their speaking skill. Keywords: English speaking materials, Islamic high schools, needs analysis, validity, ESP